The African American religious experience in America - Pinn, Anthony B. (The American religious experience, 2006)
Introduction -- Historical context of the African American religious experience -- Development of the African American religious experience -- Black spiritual churches -- Buddhism -- Humanism -- Judaism -- Nation of Islam -- Protestant churches -- The Roman Catholic Church -- Santería -- Sunni Islam -- Voodoo.